Sabotage and Deterrence Incentive in Tournament: An Experimental Investigation and Policy Implications - Kingsuwankul, Sorravich (Thammasat Review of Economic and Social Policy, 2017)
This research analyzes the impact of deterrence incentive on sabotage behavior in rank-order tournament using experimental method. Laboratory findings confirm Becker’s deterrence hypothesis in a tournament setting. Implementing punishment suppresses sabotage behavior. In addition, increasing probability of inspection is more effective than increasing the magnitude of penalty despite equivalence of expected punishment. Furthermore, analysis of the data reveals existence of cognitive biases influencing sabotage behavior. Findings also suggest that perceived legitimacy of the enforced rule and regulations is important. This study supports existing theoretical frameworks pertaining to tournament and economics of crime, and also provides policy implications for contest designers.